1992
DOI: 10.1111/j.1600-0773.1992.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathinone, a Natural Amphetamine

Abstract: Cathinone is an alkaloid that has been discovered some fifteen years ago in the leaves of the khat bush. This plant grows in East Africa and in southern Arabia, and the inhabitants of these regions frequently chew khat because of its stimulating properties. Cathinone, which is S(-)-alpha-aminopropiophenone, was soon found to have a pharmacological profile closely resembling that of amphetamine; indeed, in a wide variety of in vitro and in vivo experiments it was demonstrated that cathinone shares the action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
185
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(191 citation statements)
references
References 53 publications
4
185
0
2
Order By: Relevance
“…These phenylpropylamines, structurally related to amphetamine and ephedrine, are considered the major bioactive compounds in khat extract (Kalix, 1992). To our knowledge, these khat-specific phenylpropylamines have not previously been reported to be associated with induction of apoptosis.…”
Section: Hl-60mentioning
confidence: 88%
See 1 more Smart Citation
“…These phenylpropylamines, structurally related to amphetamine and ephedrine, are considered the major bioactive compounds in khat extract (Kalix, 1992). To our knowledge, these khat-specific phenylpropylamines have not previously been reported to be associated with induction of apoptosis.…”
Section: Hl-60mentioning
confidence: 88%
“…Cathinone is a major alkaloid component in fresh Catha leaves, but is relatively unstable and is rapidly metabolised into norpseudoephedrine (cathine) and norephedrine. Other alkaloid compounds such as the phenylpentenylamines and cathedulines could also contribute to pharmacological effects of khat (Kalix, 1992;Al-Motarreb et al, 2002). Most of their pharmacological effects are suggested as being mediated by release of biogenic amines through preferential binding to the norepinephrine receptor/transporter, but also partly through binding to dopamine and 5-hydroxytryptamine receptors (Rothman et al, 2003).…”
mentioning
confidence: 99%
“…Cathinone is a natural amphetamine-like alkaloid found in the fresh leaves and stems of the African shrub Khat (Catha edulis) (Kalix, 1992). The systematic name of mephedrone is 2-(methylamino)-1-(p-tolyl)propan-1-one(2S)-2-(methylamino)-1-(4-methylphenyl)propan-1-one, in accordance with the International Union of Pure and Applied Chemistry.…”
Section: Chemistrymentioning
confidence: 99%
“…Along with cathinone, other less potent stimulant substances are also present in khat leaves, namely norephedrine and norpseudoephedrine (cathinone) [5]. Taking into account the structural and pharmacological properties of amphetamine and cathinone, it can be concluded that they should act similarly by inducing dopamine releases from central dopaminergic nerve terminals, thus increasing the activity of dopaminergic pathways [6,7].…”
Section: Introductionmentioning
confidence: 99%